2020
DOI: 10.1016/j.jinf.2020.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the FebriDx host response point-of-care test in patients hospitalised with suspected COVID-19

Abstract: Introduction: Management of the COVID-19 pandemic is hampered by long delays associated with centralised laboratory PCR testing. In hospitals this leads to poor patient flow and nosocomial transmission and so rapid, accurate diagnostic tests are urgently required. The FebriDx is a point-of-care test that detects an antiviral host response protein in finger prick blood within 10 min, but its accuracy for the identification of COVID-19 is unknown. Methods: We performed a real-world diagnostic accuracy study of F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 17 publications
3
61
4
2
Order By: Relevance
“…10 Even faster, finger-prick host response point-of-care testing also has the potential to streamline triage and patient care decisions. 32 In conclusion, this study of adults presenting to hospital with suspected COVID-19 shows there are significant differences in the clinical characteristics, symptoms, and clinical outcomes of patients testing positive and negative for SARS-CoV-2 infection. These data can be used to inform healthcare planning in preparation for the next phase of the pandemic.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…10 Even faster, finger-prick host response point-of-care testing also has the potential to streamline triage and patient care decisions. 32 In conclusion, this study of adults presenting to hospital with suspected COVID-19 shows there are significant differences in the clinical characteristics, symptoms, and clinical outcomes of patients testing positive and negative for SARS-CoV-2 infection. These data can be used to inform healthcare planning in preparation for the next phase of the pandemic.…”
Section: Discussionmentioning
confidence: 73%
“…These challenges may be addressed by implementing molecular point-of-care testing for SARS-CoV-2 [10] . Even faster, finger-prick host response point-of-care testing also has the potential to streamline triage and patient care decisions [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The SwabSeq diagnostic platform complements traditional clinical diagnostics tests 25 , as well as the growing arsenal of point-of-care rapid diagnostic platforms 26 emerging for COVID-19, by increasing test capacity to meet the needs of both diagnostic and widespread surveillance testing. Looking forward, SwabSeq is easily extensible to accommodate additional pathogens and viral targets.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with a high probability of a SARS-CoV-2 infection should be tested with priority if testing resources are limited. Recently, Clark et al reported that the FebriDx point-of-care test which is based on the detection of the antiviral host response protein MxA had high accuracy to identify COVID-19 during the first wave 1 . They suggested that in hospitals, MxA positive patients should have a PCR test for confirmation or exclusion of COVID-19 with priority.…”
mentioning
confidence: 99%